Race to the Top. Georgia Report. Year 4: School Year 2013-2014. [State-Specific Summary Report] (US Department of Education, 2015)
This State-specific summary report serves as an assessment of Georgia's annual Race to the Top implementation. The Year 4 report for Phase 2 grantees highlights successes and accomplishments, identifies challenges, and provides lessons learned from implementation from approximately September 2013 through September 2014. To support implementation of the Common Core Georgia Performance Standards (CCGPS), the State made over 18,000 CCGPS-aligned resources in English Arts (ELA), mathematics, science, and social studies available through the State's longitudinal data system (LDS), specifically the Teacher Resource Link. In SY 2013-2014, the State continued to support implementation of its Assessment Literacy professional learning course, "Georgia Formative Instructional Practices: The Keys to Student Success," designed to support teachers to use formative assessment to improve instruction. Throughout SY 2013-2014, nearly 60,000 educators in 133 local education agencies (LEAs) (which represent approximately 53 percent of teachers statewide) were engaged with the Formative Instructional Practices modules. In SY 2013-2014, the State implemented its educator evaluation system for leaders and teachers of tested grades and subjects in its Race to the Top participating LEAs; (4) In May 2014, the State finalized its Teacher Effectiveness Measure (TEM) and Leader Effectiveness Measure (LEM) rubrics and provided all educators with their final SY 2013-2014 ratings in June 2014, which include student growth on State assessments if applicable. Per the State's amended timeline, in SY 2014-2015 teachers of non-tested grades and subjects in Race to the Top participating LEAs will receive their first rating that includes student growth on Student Learning Objectives (SLOs). To support local SLO development, the Georgia Department of Education (GaDOE) compiled nearly 3,000 assessment items for 74 courses developed with educators during SY 2012-2013 for statewide use in developing SLOs. In response to demand from the field, GaDOE staff held 10 regional Content Week Sessions across the State to develop SLO pre- and post-assessments and items in high-need subjects. SLO assessments developed during these content weeks were made available for use in SY 2014-2015. As a result of substantial progress in Years 3 and 4, the Department removed Georgia from high-risk status for activities related to implementation of its educator evaluation system in January 2015. Georgia experienced some challenges in year 4. Due to previous delays, educators did not have access to benchmark assessments and professional learning courses on the CCGPS during SY 2013-2014. Although the State made formative assessment items available to educators in SY 2012-2013 and SY 2013-2014, Georgia was not able to track usage of those items. The Department continues to withhold nearly $10 million of the State's Race to the Top funds associated with performance-based compensation, and the Department continues to hold conversations with the State regarding these funds. Looking ahead to year five, Georgia will continue to support LEAs as they transition to new assessments in SY 2014-2015 utilizing the resources that were created through Race to the Top. GaDOE will also continue to expand its LDS, adding new features to personalize instruction for students and provide opportunities for teachers to interact and share resources with one another. During the no-cost extension period in SY 2014-2015, or Year 5, the State will continue to support implementation of its teacher and leader evaluation system in all LEAs across the State through additional training and support to effectively prepare and build capacity in all LEAs to successfully implement the system. In Year 5, GOSA will use Race to the Top funds to continue working on an evaluation of the State's lowest-achieving schools. Finally, the State will continue to support participating LEAs and implementation of its Race to the Top grant. Participating LEAs in Georgia have budgeted approximately $43,000,000 in Race to the Top funds to support ongoing work in Year 5, representing approximately 22 percent of the LEA portion of Race to the Top funds. A glossary of terms is also included. [For "Race to the Top. Georgia Report. Year 3: School Year 2012-2013. [State-Specific Summary Report]," see ED580316.]